(untitled) (Research, Society and Development, 2021)
Inflammation is a response to infection or tissue damage that occurs to eliminate microorganisms or irritating agents and to enhance tissue repair, being the body’s first defense against aggression. Inflammation can be treated with Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and these are the most consumed drugs in the world. The present work aims to analyze the profile of NSAIDs dispensing in a pharmacy in the interior of Bahia, specifying which NSAIDs are most dispensed in the establishment. It consists of a descriptive and qualitative and quantitative cross-sectional study carried out in the municipality of Itarantim located in the center-south of Bahia. The results revealed a total dispensation of 6,166 NSAIDs between the months of March and June 2021, with the highest dispensation in May (27.80%) and the month of March with the lowest number of dispensations (21.05%). A total of 49.22% of the formulations contained only one active ingredient, while the number of associated formulations was equivalent to 50.78%. Among the isolated formulations, the three most dispensed were dipyrone (29.52%), followed by nimesulide (20.92%) and AAS (16.84%). Among the associated formulations, 3,131 in total, the three most dispensed were Caffeine + carisoprodol + diclofenac + paracetamol (33.73%), dipyrone + orphenadrine + caffeine (20.25%), paracetamol + chlorpheniramine + phenylephrine (25.24%). NSAIDs are a class of high dispensation in the drugstore studied, being greater in the months of May and June. It was also possible to conclude that self-medication is frequent in relation to the use of these medications.